Dissecting Gender and Power Dynamics in Indonesian Online Media - Mustafa, Mustafa; Alhidayatillah, Nur; Rohayati, Rohayati; Fitriyyah, Mustiqowati Ummul; Soim, Muhammad; Ginda, Ginda (Universitas Muhammadiyah Ponorogo, 2025)
Political women in Jane Ahlstrand's view have always attracted greater attention because of their differences with masculine political norms. (Subedi et al., 2023).Â In the context of socio-political change, prominent political figures can become icons through which ideological boundaries and power relations are contested and redefined in various discursive platforms. Women in the world of politics have become media icons that are very prominent in the conditions of socio-political transformation. (J. Ahlstrand, 2023). One of Ahlstrand's works is Women, Media, and Power in Indonesia,Â a book published by Routledge, sponsored by the Asian Studies Association of Australia (S. Ahlstrand, 2019). This book shows the important relationship between gender and power structures in democratic Indonesia, and the role of online media in regulating these power relationships (Robinson, 2020; Sakai, 2021). By using critical discourse analysis (CDA) as a theoretical framework (Fairclough, 2015), and social actor analysis as a methodological approach (Leeuwen, 2008). This study examines the discursive representation of three Indonesia women political figures, namely the Chairperson of the Indonesia Democratic Party of Struggle (PDIP) Megawati Soekarnoputri, the Mayor of Surabaya Tri Rismaharini, and the Minister of Maritime Affairs and Fisheries Susi Pudji Astuti (Aspinall, 2019; Crouch, 2021).The three are the most popular and influential figures in Indonesia representing three institutions, namely political parties, regional heads, and ministries (Budiardjo, 2020; Honna, 2019). These three female political leaders have attracted the attention of the public and the media because they are considered to represent the hopes and anxieties of the nation in a period of transition (Crouch, 2021; Sulistiyanto, 2019). This book shows the important relationship between gender and power structures in democratic Indonesia, and the role of online media in regulating these power relationships (S. Ahlstrand, 2019; Sakai, 2021). This report presents new linguistic evidence in the form of a discourse strategy that reflects the dynamic relationship between women and power (Fairclough, 2015; Sakai, 2021). In the context of political transitions where power structures have historically been gendered, women occupying non-traditional positions of power can become iconic figures because of their striking differences from male political norms (Aspinall, 2019; Leeuwen, 2008). Although their presence in politics